Tra sparizioni e ricomparse, conoscenza e rifiuto: una lettura dell’immagine femminile nel cinema degli anni Settanta e Ottanta - Traverso, Paola (Il sogno della farfalla, 2026)
The aim of this essay is to investigate the transformations of the female image which occurred in the European cinema from the late 1970s to the mid-1980s, within the context of cultural and aesthetic upheaveals, following the 1968 crisis. Through an analysis of Buñuel and Antonioni works, it highlights representations of the female image characterized by disappearance or loss and the elusiveness of the object of desire. These may symbolize a progressive dematerialization of the female body, linked to an abstract and cold conception of sexual liberation. Such context is examined in dialogue with Massimo Fagioli’s thought, particularly his idea of relationship as knowledge, considering Tarkovsky’s Andrej Rublëv and the conceptualization of the “peasant” image in his theoretical writings, later reflected in Bellocchio’s film La condanna. A crucial turning point is represented by Bellocchio’s film Diavolo in corpo, and Fagioli’s decisive influence in shaping a new, unprecedented female image. Finally, a brief discussion of Montaldo’s movie Giordano Bruno is included to evoke resonances between Bruno and Fagioli, closing with a reflection on resistance and ongoing search, rejection and rebellion, as expressions of a healthy human identity opposed to the death instinct, repressive paternal figures, and divine thought.